2019
DOI: 10.1016/j.heliyon.2019.e01735
|View full text |Cite
|
Sign up to set email alerts
|

Health Information Technology Acceptance Framework for diabetes management

Abstract: This study examined the level of acceptance of Health Information Technology (HIT) as tools for diabetes care and management, in six selected tertiary hospitals in southwestern zone of Nigeria. Using both quantitative and qualitative methods, this study was conducted amongst selected healthcare stakeholders namely Nurses, Doctors, Laboratory Scientists, Pharmacists, ICT unit Professionals, Medical Record Officers, and Type-2 diabetes out-patients available in the designated hospitals. Adapting Technology Accep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…The TAM's evaluation method have advantages in evaluating systems, such as, seeing two aspects of perceived usefulness and perceived of use (Ayanlade et al, 2019), UTAUT of performance expectancy, effort expectancy, social influences, and facilitating conditions (Gunawan, 2018). Both methods only assess whether the system being evaluated is acceptable to the user, but it is not seen from the aspects of human, organization, technology and the benefits provided.…”
Section: Introductionmentioning
confidence: 99%
“…The TAM's evaluation method have advantages in evaluating systems, such as, seeing two aspects of perceived usefulness and perceived of use (Ayanlade et al, 2019), UTAUT of performance expectancy, effort expectancy, social influences, and facilitating conditions (Gunawan, 2018). Both methods only assess whether the system being evaluated is acceptable to the user, but it is not seen from the aspects of human, organization, technology and the benefits provided.…”
Section: Introductionmentioning
confidence: 99%
“…the positive attitude of users towards technology. The results of the study by Ayanlade et al 25 , Kindratt et al 26 and Sebetci 27 indicated that the strong understanding of staff and patients about the implementation and acceptance of HIT leads to achieving its benefits.…”
Section: Discussionmentioning
confidence: 99%
“…These types of tools were also accepted by the health care personnel, who claimed it helped them with continuous monitoring of the patient's health status, especially for patients that live in the countryside. It also helps take preventive measures sooner, relieve them unnecessary work and enables faster and easier accomplishment of their daily tasks (Ayanlade et al, 2019). Psychosocial factors which influence patients' willingness to use ICT are the patients' attitude toward ICT, the effectiveness and level of expected success of such technology, and the strive imported by the patients (Shibuta et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Others thought that their current self-management activities were enough for them or their health condition did not allow them to use ICT based tools (Shibuta et al, 2016;Petersen et al, 2018). Other barriers included fear of data insecurity, mistrust of technology and the preference of face-to-face interaction with health care personnel (Petersen et al, 2018;Ayanlade et al, 2019). It was shown that patients found ICT based tools helpful in making diabetes self-managment plans (Ayanlade et al, 2019).…”
Section: Discussionmentioning
confidence: 99%